Less-Lethal Hybrid Ammunition Wounds: A Forensic Assessment Introducing Bullet-Skin-Bone Entity - De Freminville, Humbert; Prat, Nicolas; Rongieras, Frederic; Voiglio, Eric J. (Journal of forensic sciences, 2010)
:  Agencies all around the world now use less‐lethal weapons with homogeneous missiles such as bean bag or rubber bullets. Contusions and sometimes significant morbidity have been reported. This study focuses on wounds caused by hybrid ammunition with the pathologists’ flap‐by‐flap procedure. Twenty‐four postmortem human subjects were used, and lesions caused on frontal, temporal, sternal, and left tibial regions by a 40‐mm hybrid ammunition (33 g weight) were evaluated on various distance range. The 50% risk of fractures occurred at 79.2 m/sec on the forehead, 72.9 m/sec on the temporal, 72.5 m/sec on the sternum, and 76.7 m/sec on the tibia. Skin lesions were not predictors of bone fracture. There was no correlation between soft and bone tissue observed lesions and impact velocity (correlated to distance range). Lesions observed with hybrid ammunition were the result of bullet‐skin‐bone entity as the interaction of the projectile on skin and bone tissues.